Globalization of higher education and cross-border student mobility - Varghese, NV (UNESCO, 2008)
Cross-border higher education has become an important mode for globalizing higher education. It occurs when a provider, programme, course material, teacher or student goes beyond the national boundaries. Based on the data on student mobility, the paper attempts to discuss the pattern of cross-border student flows and some plausible explanations for the observed patterns. During the colonial period, a good share of the student flow was from colonies to the world capitals. During the Cold War era, the rival powers were competing to influence the direction of the flow. During the period of globalization, it became a market-driven activity and, at times, a commercial activity traded under GATS. The recent changes in the flow of cross-border students indicate that the dominant flow continues to be toward Europe and the USA. However, countries such as Australia and New Zealand are becoming attractive destinations for overseas students. These changes in the direction of flow are influenced more by the cost of education rather than by political considerations. Many institutions in some of the host countries rely heavily on the income brought by the cross-border education students.
Keywords: coopération transnationale; globalisation; mobilité étudiante